TO STUDY AND ANALYSIS OF RTV SILICONE RUBBER INSULATOR OPERATED WITH VARIOUS TEMPERATURE - Mahobia, S.K. (International Journal of Engineering Technologies and Management Research, 2017)
The insulator are most important equipment in transmission Line, Distribution Line and electrical power plant. In this way the insulator are used with pin, insulator and pin are mounted on the frame, which is connected with the Grid power supply. The insulator has to separate of electrical power supply and structure, in this way we are used the high quality insulator.